Comparison of manual and virtual model surgery for wafer fabrication in maxillary repositioning: an in vitro study - Junho Jung; Jongseok Shin; Joo-Young Ohe; Byung-Joon Choi (Head & Face Medicine)
Abstract Background The aim of this study was to compare the accuracy of 3D-printed intermediate wafers (3DW) with conventionally made intermediate wafers (CW) fabricated through manual model surgery (MMS). This study was designed as an in vitro experiment focused on the Le Fort I osteotomy and maxillary repositioning process. It aims to achieve maxillary repositioning outcomes mediated by intermediate wafers while eliminating intraoperative errors. Materials and methods Both MMS and virtual model surgery (VMS) were performed for each patient to fabricate CW and 3DW. Subsequently, the maxillomandibular dental casts were remounted on the articulator using the fabricated CW and 3DW, followed by digital scanning and superimposition. The midpoint of the right maxillary central incisor edge, the uppermost points of the right and left maxillary canines, and the mesiobuccal cusps of the right and left maxillary molars were used as measurement points. The points in VMS were set as references for comparison. Paired t-tests were conducted to compare the outcomes between CW and 3DW. Independent t-tests were used to analyze differences between groups with and without rotational movements. Additionally, Spearman’s correlation analysis was performed to examine the relationship between the rotational movement of the maxilla and the corresponding coordinate differences. Results Significant differences were observed in the transverse (p = 0.005), anteroposterior (p = 0.016), and vertical (p = 0.003) coordinates between the maxillary positions derived from CW and VMS. In MMS, the presence of roll movement significantly influenced transverse position (p = 0.002), pitch affected vertical position (p < 0.001), and yaw impacted transverse (p = 0.005) and vertical (p = 0.019) positions. Conclusion 3DW demonstrated greater accuracy than MMS with CW. Especially in cases involving rotational maxillary movements such as roll, yaw, and pitch, it resulted in fewer errors compared to MMS with CW. Consequently, 3DW offers more precise recording of maxillary repositioning plan and contributes to the successful transfer of this plan into the surgical outcome in orthognathic surgery.